Realizing quasi-bound states in the continuum with stable resonant wavelength through compensation mechanism - Xupu Wu; Deyong Xiong; Gaofu Liu; Yonggang Wu; Maojin Yun; Deliang Chen; Xiaosi Qi (Results in Physics, 2024)
All-dielectric metasurfaces underpinned by the physics of bound states in the continuum (BICs) have surged interest due to their spectral selectivity and strong light confinement. In this work, We propose a compensation mechanism for SP-BIC with stable resonance wavelength and controllable Q-factor. Here we take metasurfaces consisting of four nano-square disks as an example to break the symmetry of the unit cell by both x-compensation and y-compensation, respectively, and the resonance wavelengths are stable. The results show that the four nanodisks are excited in two modes with x-compensation and y-compensation when only C2 symmetry is preserved, and in one mode with x-compensation and y-compensation when only σx symmetry is preserved. Multiple decomposition results show that the loop dipole and magnetic dipole dominate the modes that retain only C2 symmetry excitation. In contrast, the magnetic dipole dominates the mode that retains only the σx symmetry excitation. Both modes excited by the compensation mechanism have stable resonances with high q-factors under the condition of preserving only C2 symmetry or only σx symmetry. Metasurfaces realized by the compensation mechanism may find promising applications in enhanced light-matter interactions such as lasers, sensing, strong coupling, and nonlinear harmonic generation.